(untitled) (International Journal of Food and Nutritional Sciences, 2022)
As digital technologies continue to reshape education, the phenomenon of hyper digitalization presents both opportunities and challenges in the realms of online teaching and virtual labs. This paper conducts a comprehensive survey of the various issues arising from hyper digitalization in these educational domains. Through an exploration of technological, pedagogical, and socio-economic factors, this survey aims to elucidate the multifaceted landscape of hyper digitalization, offering insights for educators, policymakers, and stakeholders.